Peningkatan Produksi Bioetanol dari Rebung Bambu Ampel (Bambusa vulgaris) Menggunakan Sakarifikasi dan Fermentasi Simultan Terekayasa - Hendri Ropingi; Khaswar Syamsu; Irvan Setiadi Kartawiria (Yayasan Literasi Sains Indonesia, 2026)
Bamboo shoots are lignocellulosic with low lignin and high protein content. This study compared bioethanol production from bamboo shoots (Bambusa vulgaris) using conventional and engineered simultaneous saccharification and fermentation (SSF) methods. The hydrolysis process was carried out using mold (Trichoderma reesei), followed by fermentation with yeast (Saccharomyces cerevisiae). The results of proximate analysis showed that bamboo shoots contained 25.51 ± 0.46% crude protein and 18.89 ± 0.37% fiber. In addition, the levels of cellulose, hemicellulose, and lignin were measured at 28.40 ± 0.49%, 31.28 ± 0.23%, and 3.77 ± 0.40%, respectively. The results showed that the conventional SSF technique produced ethanol at 3.42 ± 0.02 g/L, with a Yp/s of 0.37 ± 0.01 g/g. After the application of aeration engineering through the engineered SSF method, the ethanol concentration increased to 4.50 ± 0.01 g L⁻¹, with a Yp/s value of 0.50 ± 0.02 g/g. The ethanol formation rate and Yp/s values ​​in the engineered SSF method were also higher, namely 0.06 ± 0.00 g/L/h and 0.50 ± 0.02 g/g compared to the conventional SSF of 0.05 ± 0.00 g/L/h and 0.37 ± 0.02 g/g. The increase in ethanol yield from the engineered SSF method was 1.35 ± 0.05 times compared to the conventional SSF method.